Taking the Wheel: Women and the Coming of the Motor Age - Scharff, Virginia (Free Press, 1991)
Though millions of women drive regularly, the image of the flighty woman driver continues to stigmatize their abilities. Scharff travels back in time to explore how the first automobiles collided with cultural and sexual notions of feminine nature and how women have influenced the car industry as a whole.
Keywords: Business History and gender; History / United States / 20th Century; Social Science / Women's Studies; Transportation / Automotive / History